Study of the average heat transfer coefficient at different distances between wind tunnel models. Issue 1 (20th January 2015) - Gnyrya, A; Korobkov, S; Mokshin, D; Koshin, A
Abstract: The paper presents investigations of physical and climatic factors with regard to design and process variables having effect on heat transfer in the building model system at different distances between them in the airflow direction. The aim of this work is to improve energy efficiency of exterior walls of buildings. A method of physical simulation was used in experiments. Experimental results on the average values of the heat transfer coefficient in the building model system are presented herein. A series of experiments was carried out on a specific aerodynamic test bench including a subsonic wind tunnel, heat models and devices for giving thermal boundary conditions, transducers, and the record system equipment. The paper contains diagrams of the average heat transfer distribution at fixed Reynolds number and the airflow angle of attack; the average values of the heat transfer coefficient for each face and wind tunnel models as a whole at maximum, medium, and large distances between them. Intensification of the average heat transfer was observed on the downstream model faces depending on the distance between models.